2007
DOI: 10.1161/circresaha.107.150755
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Myocardial and Vascular Precursor Cells in Human and Mouse Epicardium

Abstract: Abstract-During cardiac development, the epicardium is the source of multipotent mesenchymal cells, which give rise to endothelial and smooth muscle cells in coronary vessels and also, possibly, to cardiomyocytes. The aim of the present study was to determine whether stem cells are retained in the adult human and murine epicardium and to investigate the regenerative potential of these cells following acute myocardial infarction. We show that c-kit ϩ and CD34 ϩ cells can indeed be detected in human fetal and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
169
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(181 citation statements)
references
References 35 publications
9
169
2
1
Order By: Relevance
“…Thus, this finding suggests a potential role for NRG1 in cardiac progenitor recruitment. Moreover, it has been reported that c-Kit + progenitor cells can present a vascular phenotype, which might suggest that they participate in de novo vessel formation [40]. Nevertheless, we did not detect the recruitment of specific progenitors with a vascular phenotype.…”
Section: Discussioncontrasting
confidence: 78%
“…Thus, this finding suggests a potential role for NRG1 in cardiac progenitor recruitment. Moreover, it has been reported that c-Kit + progenitor cells can present a vascular phenotype, which might suggest that they participate in de novo vessel formation [40]. Nevertheless, we did not detect the recruitment of specific progenitors with a vascular phenotype.…”
Section: Discussioncontrasting
confidence: 78%
“…Immunohistological analyses reveal that canonical Wnt activity is primarily confined to endothelial cells and a-SMA expressing in mesenchymal cells. The cell lineage tracing analysis demonstrates that at least half of the subepicardial SMA 1 cells within granulation tissue are endothelial origin, possibly through EndMT (20). Similar to epicardial cells, which undergo EMT and mainly adopt myofibroblast, fibroblast, and smooth muscle cell fates after MI, endothelial cells may be an additional significant source of repair cells after infarction.…”
Section: The Role Of Endmt In Disease Progression and Tissue Regeneramentioning
confidence: 91%
“…The heart contains several cohorts of resident cardiac progenitor cells (CPCs) which have been characterized by different groups (Beltrami AP et al 2003; Oh H et al 2003, Martin CM et al 2004, Messina E et al 2004, Laugwitz KL et al 2005, Limana F et al 2007, Davis DR et al 2010) and are considered to be responsible for tissue homeostasis (Quaini F et al 2002). Because CPCs are intrinsically programmed to generate myocardium, they appear best suited for the complex task of reconstituting tissue that is lost with a myocardial infarction (Chamuleau SA et al 2009) and restoring the blood supply in the damaged area (Dawn B et al 2005).…”
Section: Resident Cardiac Progenitor Cells (Cpcs) For Heart Repairmentioning
confidence: 99%